Impact of traffic overload on road pavement performance - Pais, Jorge (2014)
Traffic on a road pavement is characterized by a large number of different vehicle types, and these can be considered in pavement design by using truck factors to transform the damage they apply to the pavement to the damage that would be applied by a standard axle. The definition of the truck factors to convert trucks into standard axles or load equivalent factors to convert axles into standard axles is carried out by considering the average loads for each axle. This process includes the vehicles that travel with axle loads above the maximum legal limit. There are also a substantial number of overloaded vehicles in terms of total vehicle weight. These axles/vehicles cause significant damage to the pavements that increases the pavement construction and rehabilitation cost. Thus, this paper investigates the impact of overloaded vehicles on road pavements by studying the truck factors for different vehicle cases applied to a set of pavements composed by 5 different asphalt layer thickness and 5 different subgrade stiffness moduli. The study revealed that the presence of overloaded vehicles can increase pavement costs by more than 100% compared to the cost of the same vehicles with legal loads.